Key Factors Exacerbate Listening Outside EFL Classrooms: Insights from Papua Indonesia - Idrus, Misnariah; Dabamona, Miftahulfadlik; Angguni, Lulu (Inspiring: English Education Journal, 2025)
This study aims to explain key factors exacerbating listening outside EFL classrooms based on the perception of English major students in a Papua university. To facilitate a comprehensive investigation into a specific real-life scenario and to enrich the researcher's understanding of the individual or incident under study, a qualitative case study design was employed. We involved thirty students majoring in English education in a university in Papua, Indonesia. Data collection was carried out using the triangulation method including reflective journals, Focus Group discussions, and semi-structured interviews. The findings show some factors promoting listening difficulties perceived by the Indonesian students: accent, tempo, dialect, and intonation. Additional factors may exist that were not raised during the data collection process. These may have been identified if more participants were interviewed. However, the sample size was limited due to time constraints. Then, measuring the impact of each factor in a quantitative study may also yield useful data.